(untitled) (The Research of Medical Science Review, 2025)
Objectives: To determine frequency of meningitis in neonates labelled to be suffering from neonatal sepsis. Study design: Cross-sectional study. Place and Duration of the study: Children Hospital, Pakistan Institute of Medical Sciences, Islamabad from November-2024 to May-2025. Methodology: A total of 146 term neonates admitted with the working diagnosis of neonatal sepsis were included. All the neonates were assessed for presence of meningitis as a cause of sepsis in neonates. Meningitis frequency as a sepsis cause in neonates was stratified by various confounding variables and post-stratification analysis was performed using Chi-square test. Data was analyzed using SPSS version 22. Results: Median age of neonate was 12.00 (15.00) days. There were 88 (60.30%) male and 58 (39.70%) female neonates. Median gestational age was 39.50 (3.00) weeks. Median birth weight was 3.10 (0.30) kg. Among all NS cases, 41 (28.10%) were labelled as having EOS while 105 (71.90%) were labelled as case of LOS. Frequency of meningitis among neonates of present study who were originally labelled as a case of NS at the time of admission was 27 (18.50%). Conclusion: In neonates admitted with the diagnosis of neonatal sepsis, frequency of meningitis was 18.50%.